The Importance of Teachers Training in Relation to the Socialization of Children with Special Education Needs in the Mainstream Classrooms - Leticja Gusho; Rodika Goci (Athens Institute for Education and Research, 2024)
This article aims to highlight the importance of teachers training about inclusiveness by relying on statistical differences in teachers' perceptions of who are trained in the last five years and those who are not, in the realm of inclusive education as regards the socialization of SEN children with their class peers. The approach of this study was quantitative, and sample extraction is carried out through the stages sampling method. For the data collection, it was used a Likert scale with a Cronbach's coefficient alpha reported 0.86. The dimension of this research, "Teachers' perceptions as regards the socialization of children with SEN with peers" consists of three factors, respectively (1) "Teacher perceptions as regards the adaption of children with SEN to the group of peers", (2) "Teachers' perceptions as regards the participation of children with SEN in managing the situation", (3) "Teachers' perceptions as regards the social participation of children with SEN with their peers". The results of the "Mann-Whitney U Test" revealed significant differences in the perception of trained and untrained teachers, as regards the three factors of the study.